Karsinoma Colon - M Alief Rianza; Muhammad Sayuti (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Colorectal cancer (Ca Colon) is a malignancy originating from abnormal neoplastic masses in the epithelial tissue of the colon and rectum. It primarily affects the gastrointestinal tract, particularly the proximal colon and the distal rectum. The incidence of colorectal cancer has significantly increased since the 1900s due to economic and industrial advancements, making it the third leading cause of cancer-related deaths in both men and women in the United States. In Indonesia, colorectal cancer ranks second and third among cancer cases in men and women, respectively. This malignancy often manifests in the rectosigmoid region of the colon. Epidemiological data highlight geographical variations in colorectal cancer incidence, with higher rates observed in developed countries compared to developing nations. The etiology of colorectal cancer involves genetic and environmental factors, including dietary habits, lifestyle, and age. The pathophysiology involves genetic mutations leading to uncontrolled cell growth. Diagnosis is based on clinical symptoms, histological examination, and imaging techniques. Treatment options include surgery, chemotherapy, and radiation therapy, depending on the stage and location of the tumor. Early detection and intervention are crucial for improving prognosis and reducing mortality rates associated with colorectal cancer.